Plants Used as Fence and Fuelwood in Manang District, Central Nepal - Bhattarai, S; Chaudhary, RP; Taylor, RSL (Scientific World, 2010)
The remoteness of Manang District, Central Nepal has resulted in continued use of wild plants to meet daily needs. Local people were interviewed during 2002-2006 regarding the uses of plants as sources of fence and fuelwood. The People of Manang have been using 16 plant species (eight trees and eight shrubs) which belong to nine families and 10 genera for fence and fuelwood. The highest number of species belonged to Berberidaceae (4 species), followed by Cupressaceae (3 species), Rosaceae and Pinaceae (2 species each). Taxaceae, Elaeagnaceae, Betulaceae, Salicaceae and Juglandaceae were represented by one species each. Among 16 species recorded, eleven species including Berberis lycium, Hippophae salicifolia, Juniperus indica, Rosa macrophylla, etc., were used as fence and 11 species including Betula utilis, Juniperus indica, Pinus wallichiana, etc., were used as a source of fuelwood. Some plants are used as both fence and fuelwood. Fence plants protect crop field from damage by livestock and wild animals and prevented soil erosion by wind. The local people of TankiManang, Manang, Braka, Munji do not collect fuelwood, and furniture wood from their nearby forest these days as they did in the past and now collect from the next village (Hongde and Pisang forest). This a good example of awareness towards conservation and forest management. The forests near their villages are now named as ‘community forest'. There is a continued need for awareness among the people about forest use and its role in the environment. Key words: Awareness; Community forest; Livestock; Manang; Wild plants. DOI: 10.3126/sw.v5i5.2666 Scientific World, Vol. 5, No. 5, July 2007 107-111